THE LAW OF TRANSPARENCY AND ACCESS TO INFORMATION IN BRAZIL: THE CASE OF THE STATE OF SÃO PAULO - Lopes Fujita, Mariângela Spotti [UNESP]; de Oliveira, Marcelo Fernandes [UNESP] (FapUNIFESP (SciELO), 2023)
The implementation of the Access to Information Law (LAI), in São Paulo, is the object of this investigation, to answer the question: after regulation, what are the consequences of compliance with the LAI in the State of São Paulo? The objectives are: a) to present the principles, concepts and guidelines that supported the promulgation of Transparency and Access to Information laws in Brazil; b) demonstrate how the government of the State of São Paulo incorporated federal legislation; and c) indicate how the municipalities of São Paulo incorporated the practices of transparency, access to information and consolidation of municipal archives into local management. The results of the exploratory research revealed that: a transition is underway from the paradigm of secrecy and state control of information flows, in force in Brazil and the State of São Paulo; the reorganization of the São Paulo State Archives System (SAESP) is a consequence and a response to this process; and that at the municipal level in São Paulo, transparency and access to information practices remain limited. It is concluded that, in São Paulo, compliance with the LAI has advanced with the reorganization of the file system in the practice of public bodies and entities, but the induction of municipalities is still punctual and incipient.
A LEI DA TRANSPARÊNCIA E DE ACESSO À INFORMAÇÃO NO BRASIL: O CASO DO ESTADO DE SÃO PAULO
Keywords: Access to Information; Access to Information Law; Government of São Paulo; Municipalities of São Paulo; Transparency in the Public Sector